2011
DOI: 10.1007/s10750-011-0843-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of submerged trees in structuring fish assemblages in reservoirs: two case studies in South America

Abstract: The importance of subaquatic structures in determining fish assemblages is well documented in the literature, but few studies have examined the influence of submerged vegetation resulting from river impoundments in which arboreal vegetation was not removed. The purpose of this study was to evaluate the role of submerged trunks determining abundance and composition of fish assemblages by comparing habitats with and without them in two reservoirs of different ages. The results of this study demonstrated the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…In addition, the diet of this species is based mostly on invertebrates for juveniles and fish for adults, using natural habitat structures for predation (Casatti et al, 2001). Furthermore, despite the reservoir age and the advanced decomposition stages of trunks and branches, some remaining areas with submerged refuges are available, which are important habitat structures for fish hiding and escaping (Gois et al, 2012). Lastly, P. squamosissimus, also important in our study, is an introduced species from the Amazon basin, and the literature reports its success in reservoirs (Agostinho et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the diet of this species is based mostly on invertebrates for juveniles and fish for adults, using natural habitat structures for predation (Casatti et al, 2001). Furthermore, despite the reservoir age and the advanced decomposition stages of trunks and branches, some remaining areas with submerged refuges are available, which are important habitat structures for fish hiding and escaping (Gois et al, 2012). Lastly, P. squamosissimus, also important in our study, is an introduced species from the Amazon basin, and the literature reports its success in reservoirs (Agostinho et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Fish aggregation was observed in the vicinities of the cages from the beginning of tilapia farming, even under small‐scale experimental conditions (total area of the cages was 48 m 2 ). Although fish can be attracted by natural or artificial physical structures in aquatic ecosystems (Gois, Antônio, Gomes, Pelicice, & Agostinho, ; Rilov & Benayahu, ), the increases in species richness indicate that species that were absent at the cage site prior to cultivation were attracted to the experimental area, staying there and even becoming abundant in some cases, as was observed for P. maculatus and M. maculatus , both species that stand out for the consumption of the feed surplus that was released in the environment (Carvalho, Vidotto‐Magnoni, & Ramos, ), and A. osteomystax , probably attracted by the increased amount of zooplankton near the cages (Strictar‐Pereira et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These structures are used as spawning, foraging and shelter habitats for fishes (Sass et al, 2006). Some authors have found that littoral zones with riparian vegetation and the presence of aquatic macrophytes are positively correlated with fish diversity (Amaral & Petrere Junior, 2001;Gomes et al, 2012), and that the presence of submerged trees increases the fish abundances (Gois et al, 2012). Experimental studies also proved that enhancing the underwater habitat complexity by means of artificial reefs or natural CWH structures increases fish diversity, and affects assemblage dynamics and trophic interactions (Freitas & Petrere Junior, 2001;Ahrenstorff et al, 2009;Santos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Restoration actions in environments under anthropogenic pressures require identifying keystone structures that will help maintaining regional species diversity and biological condition (Tews et al, 2004). In lakes, keystone elements are generally related to underwater structures as artificial reefs, submerged trees or natural coarse woody debris that promote habitat heterogeneity for fishes and invertebrates (Freitas & Petrere Junior, 2001;Sass et al, 2006;Santos et al, 2011;Gois et al, 2012).…”
Section: Introductionmentioning
confidence: 99%